English-Indonesian Translation Methods in the Subtitle “Mariposa and the Fairy Princess” Movie - Utami Rosalina; Virga Putra Darma; Nunik Nur Rahmi Fauzah; Ratri Nuryani Qudwatullathifa (Journal on Education, 2024)
This research aims to analyze what is method translation English to Indonesia which used by the Mariposa and The Fairy Princess movie based on Newmark’s Theory. This research use qualitative method. Researcher use subtitle of Mariposa and the Fairy Princess has been translated from English Language (SL) into Indonesia language (TL) as the data. The results of this study is find out the method use of Mariposa and the Fairy Princess movie, that is there are 104 data use word-for- word translation method there are 33 data or use Literal Translation. There are 110 data use Faithful Translation. There are 101 data use Semantic Translation, There are 9 data use Free Translation, There are 52 data or use Idiomatic Translation. There are 10 data or use Communicative Translation. In addition ib the subtitle of Mariposa and the Fairy Princess the most used method is Faithful Translation Method.